Twenty years after the fall of the Berlin Wall: Rethinking the role of money and markets in the global economy - W. L. Hoskins; Walker F. Todd (Levy Economics Institute of Bard College, 2018)
Many of the hopes arising from the 1989 fall of the Berlin Wall were still unrealized in 2010 and remain so today, especially in monetary policy and financial supervision. The major players that helped bring on the 2008 financial crisis still exist, with rising levels of moral hazard, including Fannie Mae, Freddie Mac, the too-big-to-fail banks, and even AIG. In monetary policy, the Federal Reserve has only just begun to reduce its vastly increased balance sheet, while the European Central Bank has yet to begin. The Dodd-Frank Act of 2010 imposed new conditions on but did not contract the greatly expanded federal safety net and failed to reduce the substantial increase in moral hazard. The larger budget deficits since 2008 were simply decisions to spend at higher levels instead of rational responses to the crisis. Only an increased reliance on market discipline in financial services, avoidance of Federal Reserve market interventions to rescue financial players while doing little or nothing for households and firms, and elimination of the Treasury's backdoor borrowings that conceal the real costs of increasing budget deficits can enable the American public to achieve the meaningful improvements in living standards that were reasonably expected when the Berlin Wall fell.
Keywords: E42; E52; E58; E61; E63; 330; Too Big To Fail; Moral Hazard; Section 13(3); Credit Allocation; Domestic Price Level Stability